Investigating Students' Metacognitive Experiences: Insights From the English as a Foreign Language Learners' Writing Metacognitive Experiences Questionnaire (EFLLWMEQ) - Sun, Qiyu; Zhang, Lawrence Jun; Carter, Susan (Frontiers in Psychology, 2021)
While research on metacognitive knowledge and metacognitive strategies in second language (L2) writing has proliferated, little attention has been paid to metacognitive experiences in learning to write. This study contributes a novel 6-point Likert scale questionnaire, EFL Learners’ Writing Metacognitive Experiences Questionnaire (EFLLWMEQ), and reports insights into learners’ metacognitive experiences gathered from its use. The questionnaire was designed to investigate, first, the nature of students’ metacognitive experiences when they learn to write in English as a foreign language (EFL) and, secondly, the relationship between students’ metacognitive experiences and their writing performance. To this end, the questionnaire was developed and validated with two independent samples of 340 and 540 Chinese undergraduates whose metacognitive experiences were measured as they learned to write in EFL. Data were subjected to exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), respectively. Findings of EFA and CFA revealed a four-factor structure of students’ metacognitive experiences of EFL writing: Metacognitive estimates, metacognitive feelings, online task-specific metacognitive knowledge, and online task-specific metacognitive strategies. Results showed that students’ metacognitive experiences had positive correlations with their EFL writing test scores. Importantly, the CFA results from the sample of 540 students supported the four-factor correlated model with the best model fit, confirming the validity and reliability of the EFLLWMEQ. This study has theoretical and pedagogical implications for how learners’ metacognitive experiences can be managed in learning to write, particularly in EFL classrooms.